Geniposide suppresses thermogenesis via regulating PKA catalytic subunit in adipocytes. (December 2021) - Li, Yan; Zhang, Kuiliang; Liu, Jinxin; Liu, Shengnan; Nie, Chenzhipeng; Yan, Ying; Guan, Yanming; Fan, Mingcong; Qian, Haifeng; Ying, Hao; Wang, Li
Graphical abstract: Highlights: Geniposide suppresses the browning processing of adipocytes. Geniposide treatment reduces body temperature and cold tolerance of mice. PKA signaling is required for the inhibition of geniposide on adipocyte browning. Abstract: Geniposide has been widely found to ameliorate many metabolic diseases. The recruitment and activation of brown/beige adipocytes are effective and promising methods for counteracting obesity and related diseases. However, the effect of geniposide on thermogenesis of adipocytes and its underlying mechanism have not yet been investigated. Here, we demonstrate that geniposide (25 mg/kg) reduces body temperature and cold tolerance of mice via suppressing thermogenic genes in interscapular brown adipose tissue (iBAT) and inguinal white adipose tissue (iWAT). Consistently, geniposide (20 mg/mL) suppresses thermogenic capacity of adipocytes (brown adipocytes and 3T3L1 preadipocyte cells) in vitro. Mechanistically, geniposide reduces the level of protein kinase A (PKA) catalytic subunit and further suppresses transcription activity and protein stability of uncoupling protein 1 (UCP1), leading to reduction of thermogenic capacity in adipocytes. Moreover, pharmacological PKA activation reverses geniposide-induced UCP1 inhibition, which indicated that geniposide suppresses thermogenesis of adipocytes via regulating PKA signaling. Together, our findings suggest that geniposide is an inhibitor of fat thermogenesis, establishing a novel function characteristic of geniposide.